Ammonia loss, soil exchangeable ammonium and available nitrate contents from mixing urea with zeolite and peat soil water under non-waterlogged condition. - Omar, Latifah; Ahmed, Osumanu Haruna; Nik Ab. Majid, Nik Muhamad (Academic Journals, 2011)
Efficient utilization of urea-N in most agricultural systems is impeded by ammonia volatilization. This study investigated the effect of mixing urea with zeolite and peat soil water on ammonia volatilization, soil exchangeable ammonium and available nitrate contents, compared with urea without additives under non waterlogged condition. The mixtures significantly reduced ammonia loss by 5 to 14% compared with urea without additives (straight urea, 46% N). The pH of the soil with the mixtures was also significantly different compared with that of urea without additives. All the mixtures of zeolite and peat soil water with urea significantly improved soil exchangeable ammonium (by 42 to 76 ppm) retention compared with urea without additives. Only one mixture significantly increased soil available nitrate content. The temporary reduction of soil pH may have retarded urea hydrolysis. This encouraged beneficial formation of ammonium over ammonia hence, the significant reduction of ammonia volatilization upon the use of the mixtures produced in this study. It could be possible to improve the efficiency of urea surface-applied to high value crops by addition of zeolite and peat soil water.